Macroprudential policy in central banks: Integrated or separate? Survey among academics and central bankers - Simona Malovaná; Martin Hodula; Zuzana Gric; Josef Bajzík (Charles University in Prague, Institute of Economic Studies (IES), 2022)
We surveyed experts from academia, central banks and other regulatory institutions on the preferred institutional setup of macroprudential policy and the underlying interactions stemming from the conduct of monetary and macroprudential policy. We find substantial support for the integration setup, under which macroprudential policy is entrusted to the central bank and not to a separate institution. The most significant factors driving the respondents' views are the large degree of interdependence of the two policies, the potential information gains from keeping them 'under one roof', and a greater capability to resolve strategic conflicts. We identify non-negligible heterogeneity in the responses, especially in terms of respondents' age, managerial position and research orientation.
Keywords: C83; E52; E58; G21; G28; 330; central banking; expert survey; institutional arrangement; macroprudential policy; monetary policy